Penggunaan Media Lagu pada Pembelajaran Tematik Terhadap Kemampuan Berbahasa SDN Rejosari 01 Semarang - Alvita Nanda Safitri; Ari Widyaningrum; Mei Fita Asri Untari (STKIP Andi Matappa Pangkep, 2022)
The purpose of the study was to describe the use of song media in thematic learning on language skills at SDN Rejosari 01 Semarang. This type of research is descriptive qualitative research. Sources of research data came from students and teachers of class IV. The data used in the study were fourth grade teacher interviews and student interviews. Data obtained from observation, interviews, giving questionnaires to students and documentation. The analytical method used is data collection, data reduction, data presentation, and conclusion drawing. The results of the research analysis are the song media in thematic learning is used during the core learning activities. As long as the media song is played, students feel happy, interested, and enthusiastic. So that the use of song media can improve students' language skills. This is shown by the results of interviews with teachers and students. This statement is reinforced by the results of student questionnaires showing that 88% of the use of song media on language skills can be seen from the students' ability to increase vocabulary. The results obtained through a questionnaire on the use of song media in thematic learning on language skills were 24 respondents who were filled by students.